Basic college mathematics - Hyde, Miller O'Neill (McGraw-Hill, 2007)
Basic College Mathematics offers a refreshing approach to the traditional content of the course. Presented in worktext format, Basic College Mathematics focuses on basic number skills: operations and problem-solving with whole numbers, fractions, and decimals. Other topics include geometry, measurement, ratios, proportions, percents, and the real number system (with an introduction to algebra). The text reflects the compassion and insight of its experienced author team with features developed to address the specific needs of developmental level students.